Provenance discrimination of commercial grape juices from Argentina and Brazil based on elemental composition and chemometric methods - Canizo, Brenda Vanina; Diedrichs, Ana Laura; Londonio, Agustín; Smichowski, Patricia Nora; Pellerano, Roberto Gerardo; Wuilloud, Rodolfo German (Springer, 2024)
Fil: Canizo, Brenda Vanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina